1871-72 N.C. Pub. Laws, 115 - (:unkn) unknown (My University, 1872)
Ch. 68, §§ 1-4: That if any person shall hunt for with gun, or chase with a dog, or shall kill or destroy any deer running wild in the woods, between the fifteenth day of January and the first day of September next thereafter ensuing, unless in an enclosure surrounded by a sufficient fence, at least five feet high, and where such person shall have a lawful right so to do, the person so offending shall pay a penalty of fifty dollars
Keywords: HUNTING REGULATION